Kegiatan Edukasi Ekonomi Modern untuk Menigkatkan Literasi Finansial Digital Anak anak di Desa Tambak Osowilangun - Muhammad Afian Firmansyah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Children in Tambak Osowilangun Village have high access to digital technology, but their digital financial literacy remains very low. Technology is generally used only for entertainment and social media without an understanding of its economic value. This condition is exacerbated by limited supervision from parents, the majority of whom work in the industrial sector, leaving children vulnerable to uncontrolled consumer behavior online. This community service activity aims to equip children in Tambak Osowilangun Village with a basic understanding of modern economics. The main focus is to improve their ability to manage their finances wisely, introduce the concept of digital savings, and develop critical thinking skills so they can distinguish between needs and wants in the technology era. The program uses the Participatory Action Research (PAR) method, which involves the active participation of children through a spiral of stages: planning, action, observation, and reflection. Data was collected through participant observation to monitor the learning dynamics of participants during the educational sessions. The implementation of the activity showed a significant increase in participants' financial understanding. Children became more aware of the risks of digital fraud and began to understand how financial applications work. Through interactive discussion sessions, high enthusiasm was generated, shifting the children's mindset from mere entertainment users to financially savvy technology users. The synergy between students and the community has succeeded in fostering a disciplined and responsible economic character in the young generation in the village.